COVID-19 Pandemic and Foreign Trade Behavior in the Democratic Republic of Congo: A Non-Parametric Test Approach by Comparison of Means - LUBONGO MBILU, Yannick; LOWENGA KOYAMODJA, Logas; KANA KIWE, Junior; MUDIANDAMBU KITADI, Oscar; NGOYA KALENDA, Angel; NTUNGILA NKAMA, Floribert (Theoretical and Practical Research in Economic Fields, 2023)
This paper analyzes the behavior of foreign trade indicators, specifically exports and imports in the Democratic Republic of Congo (DRC) during the COVID-19 pandemic. This health crisis was labelled a "pandemic" by the World Health Organization because it affected all mankind to varying degrees. It also examines the evolution of international reserves during the same period, while taking stock of some macroeconomic indicators for the DRC. Non-parametric tests reveal differences in the means between the period of the COVID-19 surge and the period of the COVID-19 decline, to verify the significance of the negative or positive influence of imports and exports in the DRC.  It was fandhat during the year most affected by the pandemic, 2020 compared to the previous year, 2019, both exports and imports fell on average annually, respectively (in millions of USD) by 1,078.6 versus 1,098.6 and by 988.8 versus 1,149.1. This can be justified by the various measures taken by the government to contain the COVID-19 pandemic. Subsequently, these same indicators (in millions of USD) will increase between 2021 and 2022, respectively from 1,742.5 to 2,368.4 for exports and from 1,520.4 to 1,920.1 for imports. This increase is the result of the urgent stimulus measures taken by the government to enable the economy to cope with the multiple economic consequences of the COVID-19 pandemic. These observations were also verified by statistical tests: these show differences for independent and matched samples at the 0.05 threshold. There is a considerable difference in exports in millions of USD between those during the absence of COVID-19 and those during the presence of COVID-19. These observations were also verified by statistical tests: these provide differences for independent and matched samples at the 0.05 level. There is a considerable difference in exports (in millions of USD) between those made in the period before and those made during the COVID-19 pandemic.